Nonlinear model predictive control with real time iteration for F-16 attitude control - Kuzucu, Siyami Gürkan (Graduate School, 2024)
The enduring presence of the F-16 Fighting Falcon in global military fleets underscores its unparalleled versatility, reliability, and cost-effectiveness, decades after its initial introduction. Designed in the 1970s as a response to the need for a high-performance, multi-role fighter aircraft. Unlike conventional aircraft, the F-16's flight dynamics are significantly influenced by its relaxed static stability and fly-by-wire control system, which together facilitate a level of manoeuvrability that is both a marvel and a challenge to replicate in simulation and control algorithms. This complexity is further accentuated by the aircraft's ability to perform high-g manoeuvres and operate across a wide range of speeds and altitudes, presenting a multifaceted challenge for aerodynamicists and control engineers alike. Understanding and accurately modelling the F-16's flight dynamics are crucial for developing advanced flight control systems, such as Nonlinear Model Predictive Control (NMPC), that can leverage the aircraft's full potential while ensuring safety and efficiency. This study explores the deployment of a nonlinear Model Predictive Control (NMPC) framework for the attitude control of the F-16 fighter aircraft, underpinned by a Real-Time Iteration (RTI) optimization strategy. The study emphasizes the NMPC's capacity to adeptly manage the aircraft's nonlinear dynamics, offering a superior alternative to traditional control strategies by integrating constraints directly and optimizing control actions based on future trajectory predictions. A pivotal element of this research is the selection of the RTI method for optimization, chosen for its robustness in solving nonlinear problems and its adaptability to real-time requirements. This method ensures that the control strategy remains computationally viable while effectively managing the intricate dynamics of F-16 flight, thus facilitating real-time operational capabilities. This study consists of six chapters. In the first chapter, the aim of the thesis is discussed along with a literature review. The second chapter, titled "System Modeling and Control," covers the mathematical modeling of the aircraft, including coordinate frames, forces and moments, dynamic modeling, PID controller, nonlinear model predictive control (NMPC), and real-time iteration. The third chapter discusses the simulation environment and stability. In this context, detailed information about the JSBSim and Unreal Engine simulation environments used in the study is provided, along with discussions on the static and dynamic stability of the aircraft. The fourth chapter focuses on the implementation of the controllers. Detailed information on the implementation of PID and RTI-based NMPC is included in the study. The fifth chapter presents the simulation results of the control structures used, with results analyzed through graphs. The final chapter, the sixth chapter, discusses the general conclusions of the study, the details of the problems encountered during the implementation phases, and future research on NMPC.
F-16 duruş kontrolü için gerçek zamanlı iterasyon iledoğrusal olmayan model öngörülü kontrol
Thesis (M.Sc.) -- İstanbul Technical University, Graduate School, 2024
Keywords: Nonlinear control; Doğrusal olmayan kontrol; Model control; Model kontrolü; Optimal control; Optimal kontrol